Mendidik Cinta Tanah Air: Memperkuat Identitas Bangsa Melalui Pembelajaran Nilai-Nilai Pancasila - Muhamad Trias Firmansyah; Adwa' Allifah Safwan; Moreno Heber Fresa; Sinamo Kevin Nathanael; Razan Megasatria; Dhafin Salman; Rafi Nurfadly; Yayang Furi Furnamasari (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2024)
National identity is an important foundation for a nation, containing noble values, culture, and history that distinguish and attract the nation.In the era of rapid globalization and dynamic social change, maintaining and preserving national identity is an increasingly important challenge. Awareness of Pancasila is the key to strengthening national identity. Pancasila, as the state ideology of Indonesia, carries noble values that reflect the spirit of nationality and diversity. This research was prepared using the literature study method by accumulating and drawing conclusions from data obtained from various sources of information, resulting in the conclusion that awareness of Pancasila is key in strengthening national identity.